A trama de posições na clínica universitária de psicologia e o entrecruzamento de demandas dos/as usuários/as, estagiários/as, supervisores/as e instituição: um estudo psicanalítico. - Santos, Kyssia Marcelle Calheiros (2024)
In a university psychology clinic, just as the users complain to the interns/therapists and/or the institution, the interns also address the demands that cross their training and clinical practice. Considering the follow-ups enacted, the prolonged persistence of some cases caught our attention. Besides the cases in which this extension is needed, what can indicate the prolonged permanence of some patients? Due to the specificities of the university clinic, this research sought to question the prolonged permanence of some patients in these spaces and the impasses in building demands, taking into account the position game established by its players—users, interns, supervisors, and the institution. We held a psychoanalysis research, mainly grounded in Freudian and Lacanian studies on demand, transfer, addressing, and treatment. We conducted semistructured interviews with service-school supervisors and conversation groups with interns-therapists. The discourses and narratives were grouped into thematic axes and analyzed through the psychoanalysis interpretation method. Given the complexity that permeates the listening device offered in these services, which simultaneously merge a space to welcome people who need treatment and talk about their suffering and a space of clinic-academic training for interns, we highlight the relevance of considering the transversally crossed threads that make up the tissue of a university clinic. Far from defining an ideal follow-up time, we believe that the notion of treatment chronification is not restricted to time but is related to several aspects that permeate the treatment and that can sometimes hamper the emergence of the typical dialectics of demand. At the end of this study, we propose the construction of clinical cases as an important device to be implemented in university clinics, considering that it can help identify the transfers, contingencies, and singularities of each case amidst the position game when intercrossing the formation and assistance demands that cross each treatment.